Application of nanotechnology in animal nutrition: Bibliographic review - Yohannes Gelaye (Cogent Food & Agriculture)
Nanotechnology is the science and engineering that involves designing, synthesizing, characterizing, and applying materials in devices and systems for nanometer-scale matter control. This review explores the application of nanotechnology in animal nutrition. Its applications in this field encompass the administration of nutrients, probiotics, and the diagnosis and treatment of diseases through drug delivery. Nanoparticles can be classified into inorganic (nano-minerals), organic (proteins, fat, and sugar nanomolecules), emulsions, dispersions, and nanoclays nanopolymers. The feeding of nanoparticles has demonstrated improvements in digestive efficiency, immunity, milk, meat, and egg quality. Nano-minerals offer low dose usage and improved bioavailability, making them an effective antibiotic alternative and can also be incorporated into natural feed ingredients. Enzyme nanoparticles are protein aggregates that show their unique properties (optical, electrical). Nanotechnology is utilized in feed processing to deliver nutrients to target organs through methods like encapsulation, chelating, packing, and nanotubes without altering taste or color. Nanoparticles could be prepared using nanotools in nanotechnique such as precipitation, emulsion cross-linking, spray-drying, emulsion-droplet coalescence, etc. Nanoparticle synthesis is performed by physical (high-energy ball milling, vapor deposition), chemical methods (forming colloids), and biological methods. Despite nanotechnology applications having potential contributions to simplify life and enhance the animal industry in feed, health, and production, the challenges in human, animal, and environmental issues are also stated as the side effects of the technology.